Interaction between mathematical disposition and independent learning in distance learning success: An ex post facto study - Imam Kusmaryono; Nuhyal Ulia; Mohamad Aminudin (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This study uses an ex post facto design with the aim of knowing the interaction between the independent variables (mathematical disposition and learning independence) as a determinant of the dependent variable (learning outcomes). The sample of this study was 32 elementary school students. The data was taken through a questionnaire method and a written test. Data analysis through two-way ANOVA test with interaction factors. The results showed that was an interaction between the independent variables (mathematical disposition and learning independence) on the dependent variable (learning outcomes) with a significance level of 0.05. So it can be concluded that the interaction between mathematical disposition and learning independence is a determining factor in the mathematics learning outcomes of elementary school students in distance learning.